Characterizing location of spotted lanternfly egg masses in wooded habitat during early invasion stages - Madalinska, Katarzyna; McDougall, Robert; Nielsen, Anne L. (Frontiers in Insect Science, 2022)
The spotted lanternfly, Lycorma delicatula (Hemiptera: Fulgoridae), is an invasive planthopper from Asia that are estimated to have spread 17 km/yr since their initial detection in Pennsylvania in 2014. Lycorma delicatula is a pest to the agricultural and forestry industries in the Mid-Atlantic region of the United States, in part due to its highly polyphagous nature. Current detection relies on visual observations, unbaited traps, or eDNA surveillance in its primary hosts, including grape and hardwoods. These approaches narrow the surveillance area by concentrating on known host plants but could be further refined to narrow the search parameters from the 100+ known host plants. Because L. delicatula appears to have a strong populations buildup in wooded areas, we evaluated the relationship between egg mass presence and habitat characteristics in wooded habitats adjacent to vineyards in New Jersey at six farms within the first two years of L. delicatula detection. Habitat characteristics included distance from wood edge, and presence of a critical host plant Ailanthus altissima, and presence of Vitis spp. within 4.5 m. We identified a significant relationship between egg mass presence and Vitis spp. with an 88% probability of finding an egg mass close to a wild grapevine, dropping to 9% where grapes were absent. During the early invasion stages when this research was conducted, a two-year delay from initial detection in wooded habitats to nymphal presence in the vineyard was observed.